Performance Persistence of Equity Funds in Hungary - Dariusz Filip (Contemporary Economics)
This study examines the phenomenon of performance persistence of equity funds in Hungary in two time perspectives: 1-year and 6-month perspectives. The empirical results confirm the occurrence of performance dependence in consecutive periods. There is also a strong evidence of short-term persistence in the total horizon of the study (from the beginning of 2000 to the end of 2009), and in several sub-periods. The 1-year persistence was also found in the tested sample and, in general, depended on the measure applied. Furthermore, I observed performance reversal, which can be partly explained by trend changes in the financial markets. The persistence of equity funds performance in Hungary is shaped by market factors rather than the diversity of managerial characteristics.